Early Outcomes in Major Amputations of Patients with Peripheral Arterial Disease of Lower Limbs: A Study in a Referral Hospital in Medellín, Colombia - Acero-Murillo, Cristhian Fabian; Rosales-Parra, Nicolas Dayam; Uribe-Munera, José Andrés; Rosales-Parra, Miguel Ángel; Timarán-Rodríguez, René Fernando (Iatreia, 2022)
Introduction: Major amputation is a significant intervention in advanced stages of peripheral arterial disease (PAD) and has important morbidity and mortality rates. Despite being a frequently performed procedure in Colombia, local statistics on its frequency and outcomes are not available. Objectives: To analyze the morbidity and mortality in patients with lower limb PAD during the 30 days following major amputation or during the index hospitalization. To identify factors related to the outcome and characterize the population. Methods: A retrospective study of patients with lower limb PAD who underwent major amputation for acute ischemia (AI) or chronic limb-threatening ischemia (CLTI) between March 2011 and December 2019 at Hospital Universitario San Vicente Fundación in Medellín, Colombia (HUSVF). Variables related to the underlying disease and perioperative morbidity were calculated in a general analysis and by groups, according to the level of amputation. Results: A total of 558 major amputations were performed, 83.5% for CLTI. The overall mortality rate was 14.7%, with 32.6% in AI and 11.2% in CLTI. The most frequent complication was delirium (28.8%). After multivariate analysis, no influential factors were identified for fatal outcomes, except for cardiovascular complications in AI. Conclusions: In this study, the only variable related to early mortality was cardiovascular complications in patients with AI. The percentages of heart disease are lower compared to those reported in studies from other countries. The most common complication was delirium.